2016
DOI: 10.1007/s00240-016-0877-6
|View full text |Cite
|
Sign up to set email alerts
|

The management of large staghorn renal stones by percutaneous versus laparoscopic versus open nephrolithotomy: a comparative analysis of clinical efficacy and functional outcome

Abstract: The objective of this study was to analyze the outcome of percutaneous nephrolithotomy (PCNL), laparoscopic and open anatrophic nephrolithotomy (AN) for management of patients with large staghorn renal stones. We analyzed the peri-operative parameters, overall treatment costs and changes in the function of the affected kidney on technetium-99 dimercaptosuccinic acid renal scintigraphy, done before the operation and before the final follow-up visit, in 45 adults who underwent PCNL (n = 16) versus laparoscopic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…For large calculus or staghorn renal stones, PCNL may not be as effective as previously believed. A recent study reported that the more invasive the chosen procedure, the higher the one-stage stone-free rate, the lower the need for ancillary procedures and the lower the cost of hospitalization (24). A study by Mishra et al (7) reported a 68-year-old female with a staghorn stone in her right ectopic kidney, for whom a residual stone remained following two PCNL treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For large calculus or staghorn renal stones, PCNL may not be as effective as previously believed. A recent study reported that the more invasive the chosen procedure, the higher the one-stage stone-free rate, the lower the need for ancillary procedures and the lower the cost of hospitalization (24). A study by Mishra et al (7) reported a 68-year-old female with a staghorn stone in her right ectopic kidney, for whom a residual stone remained following two PCNL treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[18] This variability is most probably due to the lack of a uniform system for the definition and the assessment of these complications and due to the different ways of display. Some report only urinary complications some include extra-urinary complications and others divide complications into minor and major ones.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent publication by Aminsharifi et al 14 compared 45 adults who underwent PCNL, 16 OS, 14 or LS 15 between 2010 and 2015.…”
Section: Case Reportmentioning
confidence: 99%